2022
DOI: 10.1177/0734242x221084060
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of leftover and expired medicines by community pharmacies and their clients in Ghana

Abstract: Improper and unsafe disposal of expired and unwanted medicines could cause harm to both people and the environment and therefore it is of public health importance. The objective of the study was to determine the methods employed by community pharmacist and their clients in the disposal of unwanted and expired medicines. Furthermore, the role of the pharmacists in the assessment of clients left over medicines was also explored. A cross sectional study design was employed with a sample of 120 pharmacy staff and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…According to the findings of a local study, the prevalence of self-medication was 64.3%, and it was found that analgesics, antibiotics and cold pharmaceuticals were mostly used in this way [ 33 ]. In another study, analgesics, antibiotics and antacid pharmaceuticals came to the forefront [ 34 ]. When we compare the findings of previous studies with our finding, it is possible to say that a finding similar to the literature has emerged when the number and quantity of unused pharmaceuticals at home are taken into consideration and that the prevalence related to self-medication is one of the highest findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of a local study, the prevalence of self-medication was 64.3%, and it was found that analgesics, antibiotics and cold pharmaceuticals were mostly used in this way [ 33 ]. In another study, analgesics, antibiotics and antacid pharmaceuticals came to the forefront [ 34 ]. When we compare the findings of previous studies with our finding, it is possible to say that a finding similar to the literature has emerged when the number and quantity of unused pharmaceuticals at home are taken into consideration and that the prevalence related to self-medication is one of the highest findings in the literature.…”
Section: Discussionmentioning
confidence: 99%